Decreased Circulating T Regulatory Cells in Egyptian Patients with Nonsegmental Vitiligo: Correlation with Disease Activity - Doaa Salah Hegab; Mohamed Attia Saad Attia (Dermatology Research and Practice)
Background. Vitiligo is an acquired depigmentary skin disorder resulting from autoimmune destruction of melanocytes. Regulatory T cells (Tregs), specifically CD4+CD25+ and Forkhead box P3+ (FoxP3+) Tregs, acquired notable attention because of their role in a variety of autoimmune pathologies. Dysregulation of Tregs may be one of the factors that can break tolerance to melanocyte self-antigens and contribute to vitiligo pathogenesis. Methods. In order to sustain the role of Tregs in pathogenesis and disease activity of vitiligo, surface markers for CD4+CD25+ and FoxP3+ peripheral Tregs were evaluated by flow cytometry in 80 Egyptian patients with nonsegmental vitiligo in addition to 60 healthy control subjects and correlated with clinical findings. Results. Vitiligo patients had significantly decreased numbers of both peripheral CD4+CD25+ and FoxP3+ T cells compared to control subjects (11.49%  ± 8.58% of CD4+ T cells versus 21.20%  ± 3.08%, and 1.09%  ± 0.96% versus 1.44%  ± 0.24%, resp., P<0.05 for both). Peripheral numbers of CD4+CD25+ and FoxP3+ Tregs correlated negatively with VIDA score. Conclusion. Treg depletion with impaired immune downregulatory function might play a key role in the autoimmune conditions beyond nonsegmental vitiligo particularly in active cases. Effective Treg cell-based immunotherapies might be a future hope for patients with progressive vitiligo.